THE DEVELOPMENT OF HORIZONS OF EXPECTATION REGARDING THE ISSUE OF HOMOSEXUALITY/LESBIANISM IN ANNIE ON MY MIND BY NANCY GARDEN - Yahya Kurnia Ramadhan (English Department, Faculty of Humanities, Andalas University, 2014)
This research takes Annie on My Mind by Nancy Garden as the object. This novel carries about homosexual theme generally, and especially the issue of discrimination to the lesbian. The purpose of this study is to uncover the development of the reader responses to Annie on My Mind. The responses in this study are classified based on the period of the emergence, the responses that turned up in the first period (1982-2002) and the responses that turned up in the second period (2003-2012). Responses that turned up in each period are also divided into the pro and the contra. In the first period responses turned up lead to the question of the issue (the message). While in the second period it develops to the element of fiction. This is because of the different horizon of expectations of the readers in each period, as well as things that affect different horizon expectations. From the responses in these two periods, the work is not considered a proper education especially for students. However, this work is considered appropriate for the target readers, namely homosexuals, in terms of the content (the message) which is considered to represent the issue of homosexuals that exist in the society.Keywords: Reception Theory, Horizons of Expectation, Homosexuality, Lesbianism